The Style of Kaminah Proverbs in The Qur'an: an Analysis of Arabic Literature Studies - Aulia Fitri; Asrina; Syofyan Hadi (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2025)
This study aims to identify the stylistic forms or sighat amstal kaminah in the language of the Qur'an from an Arabic literary perspective. The focus of this study is on metaphors that are not explicitly mentioned in the wording that refers to the words tamstil, tasybih, or other words that have metaphorical meanings but still retain their metaphorical meanings. The research model used is qualitative, employing a descriptive approach. The research stages include data reduction, data display, and conclusion drawing/verification. The data collection techniques used include documentation in the form of books, Qur'anic commentaries, and journal articles. This study found that amtsal is a very distinctive literary style in conveying information and metaphors that have their own appeal and transform abstract concepts into something tangible. The results of the above study indicate that the proverb kaminah describes the expression: “The best of affairs is the middle ground” found in QS. Al-Baqarah: 68 and QS. Al-Isr?': 110, a verse similar to the expression: “News is not the same as reality witnessed firsthand” found in QS. Al-Baqarah (2): 260, a verse similar to the expression: “Whatever you borrow, you will be repaid in equal measure,” found in Surah An-Nisa (4): 123, and a verse with the expression: “A believer should not fall into the same pit twice,” found in Surah Yusuf (12:64)